Experts’ Perspective on the Development of Experiential Marketing Strategy: Implementation Steps, Benefits, and Challenges - Urdea, Ana-Maria; Constantin, Cristinel Petrișor (MDPI AG, 2021)
Consumer needs change over time as a result of the fast-paced advancement in technology and the induction of the Internet, expansion that leads to a difficulty for brands to adapt their marketing promotion strategy and trying to remain innovative and effective at meeting their consumers’ expectations. This research investigates what effect experiential marketing campaigns have on both customers’ perception and business outcomes, aiming to develop a deeper understanding of experiential marketing, its challenges, and benefits, to understand customers’ reactions to experiential touchpoints, to explore what type of technology increases experiential perceived value, and to envisage the evolution of experiential marketing strategy. To capture all the important facets of the research objectives, an exploratory survey based on the voices of 31 marketing experts from all around the world was applied. By identifying the key drivers of experiential marketing campaigns in a hybrid setting, the present study highlighted the important role that experiential marketing has as a communication strategy, offering additional insights to marketing specialists on the experiential marketing implementation steps. A theoretical framework of the steps needed to put into practice an experiential marketing strategy was proposed.